Agrifood systems policy research: historical evolution of agrifood systems in Haryana, India. Policy and institutional evolution - Narain, V. (International Water Management Institute (IWMI). CGIAR Initiative on Transforming Agrifood Systems in South Asia, 2023)
This study examines the evolution of public policy and institutions shaping the agrifood systems in Haryana, India, from 1850 to the present. Public policy is conceptualized as representing state intent (Narain 2018; Dye 2002); in the context of this study, this includes a historical review of public policy spanning the colonial as well as postcolonial eras. Institutions are conceptualized as regularized practices, norms, and codes of conduct that structure repeated human interactions (North 1990). Thereby, in this study, institutions refer to both statutory (enforced and legitimized by the state) and non-statutory (legitimatized by sources other than the state) institutions.